Особливості планування радіорелейних систем умережах мобільного зв’язку - Семенко, А. І.; Шокотько, А. А. (Видавництво Львівської політехніки, 2014)
Показано актуальність використання радіорелейних систем у мережах мобільного зв’язку, які дають змогу створювати розгалужену мережу доступу з великою пропускною здатністю і з достатньо гнучкою для зміни топологією без великих втрат коштів і часу. Зазначено, що ефективна робота радіорелейних мереж досягається технічно правильним плануванням обладнання, частот, ємностей прольотів і їх параметрів, забезпеченням прямої видимості прольоту, стійкості конструкції до вітрових навантажень, стабільності електроживлення, мінімальних завад через інтерференцію сигналів у мережі. Підкреслюється здатність радіорелейного обладнання працювати в гібридному режимі з одночасним використанням стандартів PDH/SDH спільно з IP пакетами і цим досягати універсального рішення для передавання даних на рівні доступу мобільних мереж. Showing the relevance of the use of microwave systems in the mobile networks, which make it possible to create developed access layer of the transmission network with large bandwidth and flexibility enough to change topology without great loss of time and money. It’s very actual to use the modern microwave equipment, which works in the range of frequencies, which are called E-band (70-80 Ghz), and it is possible to reach the transmission speed rates up to 2.5 Gb/s. Such transmission speed is enough to satisfy the need not only of 3G base station, but LTE as well. It is noticed, that in the countryside and in small towns concentration of base stations is reduced in comparison with cities, as each station can cover a large area due to fewer obstacles to propagation of radio waves and a low density of subscribers. In such cases, microwave equipment that combines the advantages of low cost and high performance with characteristics that can compete with the wire communications, also is the best solution for the deployment of transmission networks on access levels. It is noted that the effective operation of microwave networks is achieved technically by the correct technical planning of the equipment, frequencies, capacities spans and their parameters, providing direct visibility of the microwave link, stable design of the supporting structure considering its wind loads, power sources stability, minimal losses caused by interfering signals in the network. In the current work the main requirement to the microwave networks structure and performance in the mobile operators transmission networks during the planning and implementation stages are described. The mains point and stages of the microwave transmission networks planning process are listed. The features of microwave transmission systems are described: signal in a radio link can be transmitted with vertical or horizontal polarization, vertical polarization signal is less affected by natural rainfall, but during the frequency planning it is often necessary to use horizontal polarization signal, the microwave stations are commonly used parabolic antennas with aperture diameter up to 2m. Depending on the microwave network geographical position it is necessary to take into the account local terrain and climate conditions, which have strong impact on the microwave links performance and microwave network planning. Also, it is possible to estimate microwave planning quality by calculating special indexes which can show the microwave network work availability, frequency planning efficiency. Emphasized the ability of microwave equipment to work in hybrid mode while using the standard PDH/SDH together with IP packets and thus achieving universal solution for data -level access to mobile networks.
Features of microwave transmission planning in the mobile networks
Keywords: мережа доступу; радіорелейна станція; радіорелейна мережа; планування мережі; топологія вузлів; пряма видимість; завмирання сигналу; access network; microwave transmission; microwave network; network planning; network topology; line of sight; signal fading